PROCRASTINATION, ACADEMIC STRESS, AND HADITH-BASED TIME MANAGEMENT AMONG STDI IMAM SYAFI’I JEMBER STUDENTS - Muhammad Athhar Dhiya; Muhammad Haikal Ali Basyarahil; Marwan Mas'ud (Yayasan Amanah Nur Aman, 2026)
This study aims to examine the relationship between academic procrastination and academic stress among students of STDI Imam Syafi'iJember from the perspective of hadiths on time management. The study employed a quantitative approach with a correlational research design. The population consisted of 1,506 students, and a sample of 94 students was selected using a simple random sampling technique. Data were collected through Likert-scale questionnaires and analyzed using SPSS version 27, including validity, reliability, normality, linearity, and Pearson Product-Moment correlation tests. The results revealed a positive and significant relationship between academic procrastination and academic stress, with a correlation coefficient of 0.416 and a significance value of 0.001. These findings indicate that higher levels of academic procrastination are associated with higher levels of academic stress among students. The dominant factors contributing to procrastination were poor time management and psychological anxiety regarding unfinished academic tasks. From the perspective of hadith, procrastination reflects negligence in utilizing time, which is regarded as a trust (amanah) bestowed by Allah SWT. Therefore, strengthening time management skills based on Islamic values is essential to reduce academic procrastination and alleviate academic stress among university students